Preliminary in-vitro study on antibacterial activity of swiftlet bird's nests - R., Suriya; Zakaria, Zunita; Yusoff, Rosnina; A., Fadzillah; Hassan, Latiffah (Universiti Putra Malaysia Press, 2004)
South East Asia's edible nest swiftlets (Aerodramus sp) is one of the most unique birds in the world. Many believed that the nest produced by this species helps to increase immunity in the body and especially to cure respiratory problems. However, there is no scientific evidence that the bird's nests can do such wonders. In this study, antibacterial activity was tested on three types of edible swiftlets' nests: white, yellow and red nests. The nests were processed into powdered and extract forms and tested against six types of bacteria: Staphylococcus aureus, Streptococcus sp., Escherichia coli, Salmonella sp., Klebsiella pneumonia, and Pasteurella multocida. Our results showed that the powdered form did not inhibit the growth of all six types of bacteria. On the other hand, the yellow nest extracts were found able to inhibit the growth one bacterial species, that is, Pasteurella multocida. As a conclusion, the results obtained from this study are not substantial to prove antibacterial effect of swiftlet's nest. However, in depth exploration on antibacterial activity of the bird's nest needs to be carried out.